(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2020)
This research examines how a handful of Yemeni refugees who arrived in South Korea are depicted in the online media news reports of the country. A total of 73 articles were collected from five different Korean English news outlets. The representation of social actor theory and conceptual metaphor theory were used in the analysis of the data. The outcomes of the analysis indicate that these Yemeni refugees are undesirably represented by the South Korean media. The continuance of such undesirable representation of these groups by the media, which is well-known for its influence on the public’s frame of thought, endangers their existence. It is hoped that the multi-layered analysis of discourse that this research offers will provide awareness to readers about the way blameless Yemenis are negatively rendered in the online media news reports of South Korea.